Is it possible to do theology without philosophical presuppositions? - D. F. M. Strauss (Acta Theologica)
Particularly in connection with the doctrine of God the unavoidability of philosophical presuppositions becomes apparent. The uncritical theological practice to speak about a concept of God is in need of the epistemological distinction between concept and idea, which is philosophical in nature. If this foundational distinction is ignored one easily ends up with a theo-ontological duplication of the diversity within creation. Terms which are actually employed within the context of an idea (in the sense of exceeding the limits of concept formation) may then be misunderstood. Such (creational) terms are then lifted from their given creational context and in an “original” sense positioned with/in God (as “essential properties”). The (theo-ontological) circle is completed when these “properties” (for example the infinity of God) are then, in a derivative sense, brought back to the domain of creation from where it was “kidnapped” in the first place. The fact that concept formation always proceeds in terms of universalia, on the other hand implies that one can only talk about a concept of God if God is no longer unique (in the biblical sense that there is but one true God). Alongside many other “gods” God would then have to conform to a universal law for “being God”. But since it is only characteristic of created entities that they are subject to the order which God as Creator has set for them, this ultimately entails that grasping God in a concept subjects God to a creational law. The distinction between concept and idea is also elucidated with reference to conceptual and idea-usages of the term constancy (inertia). All in all our argumentation fits within the context of a new account to address in a meaningful way (also in scientific theological parlance) the possibility to employ creational terms in talking about God while at the same time honoring God’s transcendence.